Crystallinity Tuning of Na3V2(PO4)3: Unlocking Sodium Storage Capacity and Inducing Pseudocapacitance Behavior. Issue 4 (11th December 2022) - Ma, Hongyang; Zhao, Bangchuan; Bai, Jin; Wang, Peiyao; Li, Wanyun; Mao, Yunjie; Zhu, Xiaoguang; Sheng, Zhigao; Zhu, Xuebin; Sun, Yuping
Abstract: As a promising cathode material of sodium‐ion batteries, Na3 V2 (PO4 )3 (NVP) has attracted extensive attention in recent years due to its high stability and fast Na + ion diffusion. However, the reversible capacity based on the two‐electron reaction mechanism is not satisfactory limited by the inactive M1 lattice sites during the insertion/extraction process. Herein, self‐supporting 3D porous NVP materials with different crystallinity are fabricated on carbon foam substrates by a facile electrostatic spray deposition method. The V 5+ /V 4+ redox couple is effectively activated and the three‐electron reactions are realized in NVP for sodium storage by a proper crystallinity tuning. In a disordered NVP sample, an ultra‐high specific capacity of 179.6 mAh g −1 at 0.2 C is achieved due to the coexistence of redox reactions of the V 4+ /V 3+ and V 5+ /V 4+ couples. Moreover, a pseudocapacitive charge storage mechanism induced by the disordered structure is first observed in the NVP electrode. An innovative model is given to understand the disorder‐induced‐pseudocapacitance phenomenon in this polyanion cathode material. Abstract : The V 5+ /V 4+ redox couple in Na3 V2 (PO4 )3 (NVP) can be activated through a proper crystal phase controlling method based on the characteristics of NVP. The obtained NVP material has an ultra‐high specific capacity of 179.6 mAh g −1 . In addition, the disordered structure in NVP can induce pseudocapacitance behavior, which is caused by the reduced interaction force between the inserted ions.